Liquid chromatography in biomedical analysis - Hanai, Toshihiko (Journal of chromatography library, 1991)
This book presents a guide for the analysis of biomedically important compounds using modern liquid chromatographic techniques. After a brief summary of basic liquid chromatographic methods and optimization strategies, the main part of the book focuses on the various classes of biomedically important compounds: amino acids, catecholamines, carbohydrates, fatty acids, nucleotides, porphyrins, prostaglandins and steroid hormones. The different chapters discuss specialized techniques pertaining to each class of compounds, such as sample pretreatment, pre- and post-column derivatization, detection and quantification.